Experimental and numerical research on squat silo and large size horizontal warehouse during quasi-steady-state storage - Guangyue, Ren; Yanan, Liu; Wei, Peng; Xu, Duan; Ledao, Zhang (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Traditional method to prevent stored grain from deterioration is to control grain temperature. A three dimensional (3-D) numerical model was established to study the temperature variation in outdoor squat silo and large size horizontal warehouse at quasi-steady-state. In this research, porous media model and solar radiation model were adopted. Numerical and experimental results showed that grain temperature was influenced by temperature of wall, height of grain and the distance between grain and the wall. Temperature changes dramatically at the top layer of grain heap due to solar radiation and heat convection at air layer. Temperature of grain close to wall increased with the increasing of ambient temperature. The model established in this research is suitable for predicting grain temperature in outdoor squat silo and large size horizontal warehouse. Keywords: squat silo, large size horizontal warehouse, porous media model, solar radiation model, three dimensional numerical model, grain temperature, quasi-steady-state storage DOI: 10.3965/j.ijabe.20160906.1729 Citation: Ren G Y, Liu Y A, Peng W, Duan X, Zhang L D. Experimental and numerical research on squat silo and large size horizontal warehouse during quasi-steady-state storage. Int J Agric & Biol Eng, 2016; 9(6): 214－222.